Norms on the Gender Perception of Role Nouns: Gender Ratio Data for Chinese, Finnish, and Russian - Gabriel Ute; Kim Jonathan; Öttl Anton; Gygax Pascal; Cui Lei; Hyönä Jukka; Nagel Olga (Ubiquity Press Ltd., 2025)
The perceived gender ratio of 422 role nouns was evaluated by Chinese- (N = 80), Finnish- (N = 77), and Russian-speaking (N = 134) students using an 11-point rating scale with counterbalanced scale anchors. Data were collected online between 2015 and 2019, via a self-administered questionnaire. The dataset contains all role nouns in English together with their Chinese, Finnish, and Russian translations, as well as by-item analyses. The data set expands previous data sets and provides social scientists with gender ratio information when selecting social or occupational roles as stimulus materials for experimentation, especially for cross-linguistic or cross-cultural studies.